#StayHomeForGrandma – Towards an analysis of intergenerational solidarity and responsibility in the coronavirus pandemic. Issue 1 (2020) - Ellerich-Groppe, Niklas; Schweda, Mark; Pfaller, Larissa
Abstract: In times of the coronavirus pandemic, many public statements appeal to intergenerational solidarity and responsibility. To clarify the normative implications of such appeals, we provide an overview of the concepts and their use in current media discourses. Mutual moral expectations between older and younger generations are (re-)negotiated. A closer sociological and moral philosophical analysis is necessary to understand the "moral economy" of intergenerational relations and the legitimacy of the claims involved.